Biblijne Megiddo w świetle rezultatów badań archeologicznych - Ronowska, Ewa (Collectanea Theologica, 2019)
The starting point of the article is to explain the reasons why Megiddo was one of the most important Canaanite cities in the northern Palestine, as well as the presentation of scientific proposals explaining the etymology and meaning of its name. In this context, considerations regarding the Bible narration associated with Megiddo and references to it contained in extra- -biblical sources are included. The second part of the article presents an outline of the history of archaeological research in Tel Megiddo, which is the starting point for presenting the history of biblical Megiddo in the light of the results of these studies. The article presents various, often contradictory, views of researchers on the history of Megiddo based primarily on the analysis of archaeological data, from the Neolithic, through the Early, Middle and Late Bronze Ages to the Iron Age.